2011
DOI: 10.2340/00015555-1075
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Uraemic Xerosis and Pruritus

Abstract: A total of 334 end-stage renal disease patients with moderate-to-severe uraemic xerosis were surveyed for quality of life assessment, using the generic Short-Form (SF-12) scale and the Dermatology Life Quality Index (DLQI). In parallel, the intensity of xerosis at four sites (the two lower legs, chest, forearm without arterio-venous shunt) was assessed, using a five-point lesional intensity score. Pruritus was auto-assessed by the patients, using a 100-mm visual analogue scale. Uraemic xerosis patients had a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 3 publications
3
16
0
3
Order By: Relevance
“…29,30 Its mean prevalence of 72% in our cohort is in keeping with those earlier results. Xerosis cutis is caused by atrophy of sweat- and sebaceous-glands and disturbed dermal hydration, at times attributed to the use of diuretics.…”
Section: Review Of Findingssupporting
confidence: 93%
“…29,30 Its mean prevalence of 72% in our cohort is in keeping with those earlier results. Xerosis cutis is caused by atrophy of sweat- and sebaceous-glands and disturbed dermal hydration, at times attributed to the use of diuretics.…”
Section: Review Of Findingssupporting
confidence: 93%
“…The patients who reported pruritus experienced a greater impact on QoL compared to non-pruritic ESRD patients ( p < 0.001). The investigators found that age and pruritus intensity, but not xerosis, independently contributed to DLQI deterioration ( p < 0.001) (Szepietowski et al 2011).…”
Section: End-stage Renal Diseasementioning
confidence: 99%
“…(Chen 2012;Finlay and Khan 1994). Investigators have used DLQI to evaluate the impact of pruritus on QoL in multiple studies, including research into ESRD (Szepietowski et al 2011) and vitiligo (Silverberg and Silverberg 2013). A pediatric version of the DLQI, the Children's Dermatology Life Quality Index (CDLQI), has been created as well.…”
Section: Instruments To Measure the Impact Of Pruritus On Qolmentioning
confidence: 99%
“…Thus, damage to the skin among ESRD patients receiving dialysis or renal replacement therapy is most likely due to UP. In addition to these anatomical consequences, UP has a major impact on the sleep quality and the psychosocial and social wellbeing of the patients91011. With continuous research in the basic health sciences, the UP prevalence has declined compared to the past.…”
mentioning
confidence: 99%